THE COMPLIMENT: ITS CONCEPTS, FUNCTIONS, COMMON TOPICS, AND TYPICAL RESPONSES IN COMMUNICATION - I Wayan Dirgeyasa (Universitas Negeri Padang, 2015)
The compliment expressions are frequently used in communication. Delivering and responding compliment is one of media to build and create good relationship between and among people when communicating. It is also considered as a politeness strategy in order to make the communication run in harmony. Generally, when someone is complimented, he or she naturally and psychologically feels excited and happy. However, few people are not really excited due to many reasons. These two different feelings of responses probably happen because responders have different perceptions and personal trait regarding to the compliment itself. Also the compliment and its typical responses are assumed likely influenced by culture to culture. This paper is an attempt to elaborate theoretically the concepts, functions, common topics, typical responses of compliment, and compliment and culture in communication and interaction.